Bundling climate information services and climate-smart practices with existing services for livestock farmers in Senegal: conceptual case with smallholder dairy farmers and commercial processing - Houessionon, Prosper; Ba, Baba; Diallo, Abdoulaye Moussa; Worou, Omonlola Nadine; Chan, Derek; Thiam, Moustapha; Wane, Abdrahmane; Whitbread, Anthony (2024)
In response to climate change challenges, integrating climate information services (CIS) and climate-smart agriculture (CSA) practices with existing services can enhance the resilience of smallholder livestock farmers in Senegal. The Laiterie du Berger (LDB) dairy plant in Richard Toll exemplifies this approach by supporting local herders through a combination of milk collection, technical support, and input provision, fostering more efficient dairy production. However, sustaining CIS-CSA services is challenging due to reliance on donor funding. The AICCRA-Senegal project aims to create a sustainable business model by integrating CIS-CSA with LDB’s operations, piloting with 200 farmers to demonstrate the benefits of this bundling approach in improving resilience, productivity, and profitability.